Comprehensive analysis of Dengue Severity during Primary and Secondary Infections by Various Dengue Virus Serotypes - Christian; Stephanie (The International Journal of Medical Science and Health Research, 2024)
Background: Dengue fever, caused by mosquitoes, has four serotypes with over 30% amino acid sequence differences. Secondary infections are more severe than primary ones, possibly due to antibody-dependent enhancement. Certain serotypes can cause more severe infections even during primary infection. Methods: The PRISMA 2020 Systematic Review ensures the accuracy and consistency of research on dengue infections. The study complies with strict inclusion and exclusion standards, assessing cross-sectional studies, English-language publications, and factors such as titles, authors, publication dates, locations, and methodologies. The aim is to improve patient care practices and raise awareness of important topics in literature. Result: After a thorough three-step screening process, 10 papers were determined to have pertinent connections to our current in-depth investigation. Following that, the entire text was closely scrutinized, and further attention was paid to these specific passages. Conclusion: Secondary infections, influenced by different serotypes, are prevalent in Southeast Asian regions, with severe cases more common than primary infections.